Disparitas Kualitas Guru dalam Pendidikan - Idin, Asep; Nurlaela, Nurlaela; Marwan, Iis (CV Bayfa Cendekia Indonesia Bekerjasama dengan Jurusan/ Program Studi Pendidikan Masyarakat FKIP Universitas Siliwangi, 2024)
Abstract. The gap in teacher quality in education is one of the main challenges affecting the quality of learning in various regions, especially between urban and rural areas. Qualified teachers determine student learning outcomes but the distribution of competent teachers is uneven. This study uses the literature review method to analyze the various factors that cause the gap in teacher quality, such as the lack of access to continuous training in remote areas, low incentives for teachers serving in these areas and limited support facilities. The study also discusses efforts that have been made, including teacher training programs, the use of technology for online learning, and government policies related to teacher placement and professional development. The findings show that although some programs have been running, the gap is still quite large, especially in rural areas that often experience a shortage of qualified teachers. Therefore, more integrated and sustainable policies are needed, including strengthening incentives, increasing access to technology-based training and improving education infrastructure in remote areas. Thus, it is hoped that the gap in teacher quality can be reduced so that all students, regardless of geographical location, can receive a quality education.